Protection of brain and pancreas from high-fat diet: Effects of catechin and caffeine - Unno, Keiko; Yamamoto, Hiroyuki; Maeda, Ken-ichi; Takabayashi, Fumiyo; Yoshida, Hirotoshi; Kikunaga, Naomi; Takamori, Nina; Asahina, Shunsuke; Iguchi, Kazuaki; Sayama, Kazutoshi; Hoshino, Minoru (Physiology & behavior, 2009)
To investigate the effect of a high-fat diet on brain and pancreas functions, we used SAMP10 mice that have characteristics of brain atrophy and cognitive dysfunction with aging. Simultaneously, we investigated the effect of green tea catechin consumption on high-fat diet feeding, because green tea catechin has been reported to improve brain atrophy, brain dysfunction and obesity. The body weight of mice fed a high-fat diet from 2 to 12 months was higher than that of the control, although the calorie intake was not. The high-fat diet also increased insulin secretion; however, the hypersecretion of insulin and obesity were suppressed when mice were fed a high-fat diet with green tea catechin and caffeine. Furthermore, brain atrophy was suppressed and the working memory, tested using Y-maze, improved in mice fed a high-fat diet containing green tea catechin and caffeine. The secretion of insulin might affect both obesity and brain function. A strong correlation was found between working memory and insulin release in mice fed a high-fat diet with green tea catechin and/or caffeine. The results indicate the protective effect of green tea catechin and caffeine on the functions of brain and pancreas in mice fed a high-fat diet.